PENGARUH ANHIDRIDA ASAM MALEAT TERHADAP SIFAT-SIFAT SABUN GONDORUKEM - Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Levopimaric acid, with its two double bonds conjugated in the same ring, can react with α-, β- unsaturated carbonyl compounds in a Diels - Alder reaction. This reaction is the basis for preparation of fortified rosin soap by addition of. maleic unhydride. The research purpose is to study the influence of maleic unhydride addition on moisture content, total rosin, combined rosin, free rosin, and unsaponifiable matter of rosin soap properties.Results indicate that the inclusion of maleic unhydride during the soap making process has a highly significant effect on the overall rosin soap properties. Furthermore. The LSD test of the difference between unfortified and fortified rosin soap properties appeared to be highly significant in favor of the fortified one. Therefore, it is advisable to fortified rosin soap for better and efficient result in the rosin size manufactures.